LE RÔLE DE L’INTERDISCIPLINARITÉ DES TRADUCTIONS PÉDAGOGIQUES DANS LA FORMATION LINGUISTIQUE DES ÉTUDIANTS EN PHILOLOGIE ROMANE - Chmiel-Bożek, Halina (Neofilolog, 2020)
Despite the growing number of academic publications discussing the advantages of translation for language learning, school teachers of French rarely use such exercises in their work with students, complaining mainly about lack of time and suitable teaching materials. Academic centres which educate future linguists offer more opportunities to use translation in practical French language classes. This article presents the opinions of students of Romance studies on the subject of translation in language learning after a semester of work with Janina Radej’s publication entitled “Francuski w tłumaczeniach. Gramatyka 1-4” [French in translation. Grammar 1-4]. It was found that for students, translation is a new and attractive exercise that diversifies the language learning process. Despite the greater effort needed, students unanimously declared that they want to do this type of exercise. They recognised not only benefits in terms of linguistic improvement, but also the interdisciplinary value, since translation exercises in the language course also offer students preparation for classes in translation studies, and serve as a prelude for doing translations in the future.